1989
DOI: 10.3109/01485018908986770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sperm Motility on Human In Vitro Fertilization

Abstract: Several sperm motility parameters in semen prepared by the swim-up technique were compared with IVF rates in 84 patients. The patients were either on clomiphene + human menopausal gonadotrophin or follicle stimulating hormone + human menopausal gonadotrophin stimulation regimens. Motility ratings were assessed both manually according to World Health Organization guidelines as well as computer-automated semen analysis (Cellsoft, Cryoresources, USA). Motility ratings of 2 2 yielded significantly higher fertiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 7 publications
0
28
0
2
Order By: Relevance
“…Mahadevan and Trouson [1984] showed an influence of sperm concentration on fertilization rate when the count fell below a level of 10 million/ml, whereas variations in sperm concentration above this level had no influence on fertilization rate. However, in support of this study, sperm motility alone was shown to be the only semen parameter to influence fertilization rate [Amann 1989;Bongso et al 1989;Donnelly et al 1998]. Further, Battin et al [1985] showed sperm motility after swim-up was also associated with the rate of fertilization.…”
Section: Discussionmentioning
confidence: 58%
“…Mahadevan and Trouson [1984] showed an influence of sperm concentration on fertilization rate when the count fell below a level of 10 million/ml, whereas variations in sperm concentration above this level had no influence on fertilization rate. However, in support of this study, sperm motility alone was shown to be the only semen parameter to influence fertilization rate [Amann 1989;Bongso et al 1989;Donnelly et al 1998]. Further, Battin et al [1985] showed sperm motility after swim-up was also associated with the rate of fertilization.…”
Section: Discussionmentioning
confidence: 58%
“…The significance of an increased VSL is still a matter of debate. Some workers [2,201 suggest that lower sperm velocities are associated with higher fertilization rates, whereas others [2, 91 show significant correlations between sperm velocity and in vitro fertilization rates. In support of the latter groups, Chiang et al [4] show pentoxifylline causing both increased sperm motility and increased penetration of hamster zona-free oocytes in asthenozoospermic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm motility is an important parameter in evaluating the fertilizing ability of semen. It has been correlated with fertilization rates of human oocytes in vitro [2] and unexplained infertility has been associated with poor motility in a disorder where a high proportion of sperm are substantially slower and less directional than sperm from normal men [21].…”
mentioning
confidence: 99%
“…Sperm motility is believed to be one of the most important semen parameters in evaluating the fertilizing ability of the ejaculated spermatozoa [Bongso et al 1989;Eimers et al 1994;Donnelly et al 1998]. It has been observed that age is associated with diminished sperm motility [Nieschlag et al 1982;Merino and Carranza-Lira 1995;Haidl et al 1996;Rolf et al 1996;Kidd et al 2001;Jung et al 2002;Eskenazi et al 2003].…”
Section: Introductionmentioning
confidence: 99%